Long-term prophylaxis of hereditary angioedema with androgen derivates: a critical appraisal and potential alternatives - Maurer, Marcus; Magerl, Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2011)
Summary Androgen derivatives are regarded as standard in the long‐term prophylaxis of swelling attacks in patients with hereditary angioedema (HAE). Because of their relatively slow onset of action, they are not suitable for acute therapy. Long‐term prophylaxis with androgen derivatives must be regarded critically, especially on account of their androgenic and anabolic effects, some of which are severe. The risk of adverse events increases with the daily dose and the duration of treatment. Thus, treatment always calls for close monitoring of patients with regard to potential adverse events. In addition, androgens are subject to numerous contraindications and they show interactions with a large number of other drugs. Off‐label use, doping issues, clarification of reimbursement and the need to import the androgen derivatives, which are no longer marketed in Germany, result in additional effort for the treating physician in terms of logistics and time involved. In symptomatic treatment of acute attacks the intravenous substitution of C1‐INH and – since 2008 – subcutaneous administration of icatibant are available. The two substances are well tolerated and their effect occurs rapidly and, when the diagnosis has been confirmed, reliably. In the light of these two treatment options for controlling acute attacks, prophylactic treatment of HAE patients with androgen derivatives such as danazol should be reassessed. Patients might benefit from a dose reduction or the withdrawal of androgen prophylaxis and attacks can be controlled with demand‐oriented acute treatment using C1‐INH or icatibant.